2008
DOI: 10.1103/physreve.78.061501
|View full text |Cite
|
Sign up to set email alerts
|

Drainage of a nanoconfined simple fluid: Rate effects on squeeze-out dynamics

Abstract: We investigate the effect of loading rate on drainage in molecularly thin films of a simple fluid made of quasi-spherical molecules (octamethylcyclotetrasiloxane, OMCTS). We find that (i) rapidly confined OMCTS retains its tendency to organize into layers parallel to the confining surfaces, and (ii) flow resistance in such layered films can be described by bulklike viscous forces if one accounts for the existence of one monolayer immobilized on each surfaces. The latter result is fully consistent with the rece… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…The experimental observation of first-order confinement-induced freezing is based on the onset of a static friction and a sudden, manyorder-of-magnitude increase in viscosity when the fluid is confined to a particular separation distance [3][4][5]7,9,10]. Other experiments observed viscoelasticity in the fluid prior to the onset of a critical shear stress [1,11,12] and a continuous transition in the viscosity [2,[13][14][15][16][17][18], leading to the conclusion that the fluid was approaching a glass transition. It has been suggested that the experimental results supporting either of these theories are fundamentally in agreement and that the conflicting models arise from differences in resolution and interpretation of the results [19].…”
mentioning
confidence: 99%
“…The experimental observation of first-order confinement-induced freezing is based on the onset of a static friction and a sudden, manyorder-of-magnitude increase in viscosity when the fluid is confined to a particular separation distance [3][4][5]7,9,10]. Other experiments observed viscoelasticity in the fluid prior to the onset of a critical shear stress [1,11,12] and a continuous transition in the viscosity [2,[13][14][15][16][17][18], leading to the conclusion that the fluid was approaching a glass transition. It has been suggested that the experimental results supporting either of these theories are fundamentally in agreement and that the conflicting models arise from differences in resolution and interpretation of the results [19].…”
mentioning
confidence: 99%
“…Two glued sheets were then re-cleaved using adhesive tape, down to a thickness of 1-4 µm. The cylindrical lenses were then mounted inside the SFA, with their axis crossed at right angle, and the exact thickness of each substrate was determined by MBI, following a procedure described in [37]. Samples were then unmounted and subjected to the various surface treatments described below in order to obtain brushes of PNIPAM covalently grafted on the substrates.…”
Section: B Surface Forces Apparatusmentioning
confidence: 99%
“…For instance, dissipation measurements with surface force apparatus show the molecular layering of simple liquids, 122,168 and enhanced polymer flows are demonstrated inside pores of dimension inferior to the radius of gyration. 169 The confinement mechanisms involved in such situations are similar to some of those at stake in separation science, as will be discussed in Section 5.5.…”
Section: Value Of B and Scaling Downmentioning
confidence: 99%